The Principal’s Role in Building a Religious and Disciplinary Culture at SD Muhammadiyah Plus Maduran - Nine Nujum; Agus Tinus; Kuncahyono (Journal of General Education and Humanities, 2026)
This study aims to: (1) examine in depth the principal’s role in developing religious culture, (2) analyze the principal’s role in fostering discipline culture, and (3) identify supporting and inhibiting factors in its implementation at SD Muhammadiyah Plus Maduran. This research employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, observations, and documentation. The research subjects included the principal, teachers, and sixth-grade students. Data analysis used an interactive model consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the principal’s role in developing religious and discipline culture is carried out through four main mechanisms: policy and program formulation, role modeling and value communication, supervision and reinforcement, as well as provision of facilities and stakeholder involvement. Religious culture is reflected in habitual worship activities, polite behavior, and moral values, while discipline culture is demonstrated through adherence to rules, punctuality, and student responsibility. These two cultures are closely interrelated, where religious values serve as the internal foundation for discipline formation. Supporting factors include teacher competence and commitment, parental support, and adequate facilities, while inhibiting factors include time constraints, student resistance, and limited resources.